Systems Engineering: Cracking the Code of Digital Transformation. Issue 1 (29th May 2019) - Peterson, Troy
ABSTRACT: While complex systems transform the landscape, the systems engineering discipline is also experiencing a transformation to a model‐based discipline. In alignment with this, the International Council on systems engineering (INCOSE) is strategically accelerating this transformation by building a broad community that promotes and advances model‐based methods to manage the high rate of change and complexity of systems today. This paper addresses contextual drivers for transformation, describes INCOSE activities aligned with accelerating the transformation, and makes the case that model‐based systems engineering can help businesses crack the code of Digital Transformation as it pertains to innovation.